Best practices for the treatment and prevention of urinary tract infection in the spinal cord injured population - Hill, Timothy C.; Baverstock, Richard; Carlson, Kevin V.; Estey, Eric P.; Gray, Gary J.; Hill, Denise C.; Ho, Chester; McGinnis, Rosemary H.; Moore, Katherine; Parmar, Raj (Canadian Urological Association Journal, 2013)
The purpose of this review of clinical guidelines and best practices literature is to suggest prevention options and a treatment approach for intermittent catheter users that will minimize UTI. Recommendations are based both on evidence in the literature and an understanding of what is currently attainable within the Alberta context, through collaboration between both major tertiary care centres (Edmonton and Calgary) and between various professionals who regularly encounter these patients, including nursing, physiatry, and urology. Key references used to prepare this document included Canadian sources such as; SCIRE, along with the American Urological Association (AUA) and European Urological Association (EUA) documents on the topic and resources from Paralyzed Veterans of America. No details on neurogenic bladder management exist in the Canadian Urological Association list of publications. Finally, the impetus for preparing these protocols arose due to concerns identified by a survey of individuals with SCI regarding perceived gaps in knowledge and practice among caregivers and physicians about SCI and UTI prevention and management.